An integrated approach of bioleaching-enhanced electrokinetic remediation of heavy metals from municipal waste incineration fly ash using Acidithiobacillus spp - Narenkumar, Jayaraman; Sathishkumar, Kuppusamy; Das, Bhaskar; Rajasekar, Aruliah; Rajakrishnan, R.; Rajamohan, Rajaram; Malik, Tabarak (Frontiers in Environmental Science, 2023)
Introduction: Municipal solid waste (MSW) incineration fly ash is a harmful residue formed during the incineration process. It contains high concentrations of hazardous heavy metals, such as lead, zinc, aluminum, and iron. Methodology: In this study, bioleaching integrated with an electrokinetic approach for heavy metal remediation from MSW incineration fly ash using Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans bacteria was tested. Results and discussion: The physicochemical properties of fly ash included a particle size of 26.1 μm, with the presence of heavy metals. A. ferrooxidans and A. thiooxidans produced sulphuric acid (0.0289 M and 0.0352 M) during the proliferation; this acid enhances the bioleaching of heavy metals from fly ash. The results of an integrated approach showed an 85%, 47%, 92%, 85%, 46%, 67% 11%, and 55% removal of the heavy metals K, Na, Ca, Mg, Al, Zn, Pb, and Mg, respectively, in the presence of A. ferrooxidans. Overall, these results evidenced that heavy metals were completely removed from the fly ash using an integrated approach. Therefore, this integrated approach can be used as an effective heavy metal removal method for treating fly ash in MSW.